Legal remedies and damages in tort law: a comparative studi civil law jurisdictions - Andi Hertawati; Alwi Jaya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study aims to analyze legal remedies and damages mechanisms in civil law in various civil law jurisdictions comparatively. The research approach uses a qualitative method with a comparative legal study design, examining regulatory frameworks, court decisions, and legal doctrines in several Continental European and Asian countries that adhere to the civil law system. The results of the study show that there are fundamental differences in the determination of the form of compensation, both material and immaterial compensation, which are influenced by legal traditions, principles of accountability, and socio-economic developments in each country. In addition, variations in the application of punitive damages as well as non-material recovery mechanisms highlight the philosophical differences between victim protection and the prevention of unlawful acts. These findings make an important contribution to the development of Indonesian civil law, particularly in the improvement of compensation regulations and the harmonization of civil liability principles at the international level. The study recommends the need for legal updates that are responsive to global dynamics and best practices from various civil law jurisdictions